EFEKTIVITAS ISOLAT-ISOLAT MIKROB RIZOSFER TERHADAP PERTUMBUHAN SEMAI Paraserianthes falcataria DAN Enterolobium cyclocarpum DI TAILING YANG TERKONTAMINASI MERKURI - Ekamawanti, Hanna Artuti; Ekyastuti, Wiwik (JURNAL AGROTROPIKA, 2020)
Utilization of rhizosphere microbes such as arbuscular mycorrhizal fungi (AMF) and mercury-resistant bacteria (MRB) is one of the alternative technologies that can be used synergisti-cally to overcome the main problem in biologically rehabilitation of marginal and mercury (Hg) contaminated tailings in ex gold mining area. The research was aimed to get an effective combination of AMF isolates (Glomus sp. SS11, Glomus sp.SS15, Glomus sp.SS18) with MRB isolates (Bacillus sp. HgTA1 and Pseudomonas HgRA) in supporting seedlings growth of sengon laut (Paraserianthes falcataria (L.) Nielsen) and sengon buto (Enterolo-bium cyclocarpum Griseb) in mercury-contaminated tailings. Dual inoculation of Glomus sp. SS15 with Bacillus sp. HgTA1 or Pseudomonas sp. HgRA isolates; dual inoculation of Glomus sp. SS18 with Bacillus sp. HgTA1 or Pseudomonas sp. HgRA isolates; single inoculation or dual inoculation of Glomus sp. SS11 with Pseudomonas sp. HgRA isolates were proven to be very effective in increasing P. falcataria seedlings height. However, only single inoculation of Bacillus sp. HgTA1 isolate was effective in increasing E. cyclocarpum seedlings height. Hg accumulation in plant tissue of P. falcataria and E. cyclocarpum, either with or without rhizosphere microbial inoculation, indicated that both plants were highly potential as Hg phytoextraction or phytostabilization agents. Key words: arbuscular mycorrhizal fungi, Enterolobium cyclocarpum Griseb, mercury, mercury-resistant bacteria, Paraserianthes falcataria (L.) Nielsen, tailings